Mostly Heterosexual and Lesbian/Gay Young Adults: Differences in Mental Health and Substance Use and the Role of Minority Stress. Issue 7 (1st September 2016) - Kuyper, Lisette; Bos, Henny
Abstract : Individuals mostly attracted to other-sex but also to same-sex partners are a distinct and common sexual orientation group with possibly increased levels of health problems. The current study examined whether mostly heterosexual individuals differed in mental health and substance use from lesbian/gay individuals and whether sexual minority risk and protective factors offer an explanation in a sample of 528 Dutch young adults (16 to 25 years old, M  = 21.2 years). Mostly heterosexual participants reported higher levels of psychological distress, suicidality, drug use, and smoking than lesbian/gay participants and equal levels of binge drinking. They also reported higher levels of internalized negativity to same-sex attractions, less openness to family members and others, less community involvement, and lower numbers of lesbian/gay/bisexual friends. However, bootstrapped mediation analysis showed that the differences in minority stress risk and protective factors did not mediate most of the differences in mental health and substance use with one exception: higher levels of psychological distress were mediated by the higher levels of internalized negativity to same-sex attractions. The limited explanatory power of the minority stress factors combined with the elevated level of problems of mostly heterosexual individuals call for future studies examining other risk and protective factors.